Rapid Nondestructive Testing Technology-Based Biosensors for Food Analysis (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The aim of this reprint is to immerse readers in the latest breakthroughs in rapid nondestructive testing (RNT) technology-based biosensors for food analysis. From electrochemical and colorimetric sensors to near-infrared (NIR) spectroscopy, fluorescence spectroscopy (FS), and hyperspectral imaging (HSI), this collection highlights novel technologies designed to ensure food safety, quality, and authenticity. In this reprint, leading experts in the field share innovative approaches to the real-time, non-invasive detection of contaminants, freshness, and nutritional components, utilizing advanced chemometrics and machine learning algorithms. Together, these studies unlock the potential of RNT biosensors to revolutionize food analysis, offering sustainable, accurate, and efficient solutions for the global food industry. This reprint provides a forward-looking exploration of how biosensor technology is reshaping food safety and quality assurance, paving the way for a more transparent and sustainable food system.